2020
DOI: 10.3390/electronics9060939
|View full text |Cite
|
Sign up to set email alerts
|

Battery Second-Life for Dedicated and Shared Energy Storage Systems Supporting EV Charging Stations

Abstract: Power systems are facing increasing strain due to the worldwide diffusion of electric vehicles (EVs). The need for charging stations (CSs) for battery electric vehicles (BEVs) in urban and private parking areas (PAs) is becoming a relevant issue. In this scenario, the use of energy storage systems (ESSs) could be an effective solution to reduce the peak power request by CSs in PAs to the grid. Moreover, II-Life battery modules are a potential approach for cutting costs and implementing sustainable solutions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Hence understanding of battery degradation is recommended during fast charging techniques adoption. [105] An economic assessment of the solution to this problem is using clustered charging stations for the sizing of energy storage systems comprising second-life batteries [93].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence understanding of battery degradation is recommended during fast charging techniques adoption. [105] An economic assessment of the solution to this problem is using clustered charging stations for the sizing of energy storage systems comprising second-life batteries [93].…”
Section: Resultsmentioning
confidence: 99%
“…There have been various techno-economic tools reported in the literature, such as Return on Investment [62,66,96], Return Rate on annual basis [89], Levelized Cost of Energy [36,91] and Levelized annual Cost of Energy using Net Present Value [93,95], Benefit-cost Ratio [61], and cost-optimization algorithms [77,80,94] for economic analysis, but these are based on several assumptions and are applicable only for specific battery compositions and controlled gridconnected applications [61,66,80,90]. These economic studies have mostly confirmed the cost benefits of second-life batteries over new batteries in terms of decrease in LCOE [91,93], increased annual revenue [36,61,70,92] and operating as well as payback years [89,90,92] but it should be noted that these results cannot be generalized. There are many uncertainties like unpredictable battery prices [92,96] and application based benefits and controlled conditions [61,69,89,90,93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic support class includes two supporting modules: data management and system management; advanced application class consists of four advanced application modules: transaction security check, electric energy measurement system, day market, real-time market, etc. The overall structure of the advanced application class is shown in figure 1 [9][10] .…”
Section: System Support and Implemen-tationmentioning
confidence: 99%
“…Given this scenario, the concept of utilizing the large quantity of batteries that would be retired for a second life stands out. The denomination used for these batteries is second-life battery (SLB), and EVs are currently being considered as the primary source of these [9]. Therefore, while providing an interesting insight into increasing battery life in EVs, more extensive research is necessary to determine when to retire these batteries, and how they can be used in a new application, a second-life application.…”
Section: Introductionmentioning
confidence: 99%